The Renaissance and Resilience of CB1 Reverse Agonists: From Central Liabilities to Peripheral Promise - R. Madhumitha Sri; R.M. Aadarshvel; S. Ravichandran* (International Journal of Cheminformatics, 2026)
Building upon these foundational insights, current research has increasingly focused on refining the pharmacological profile of CB1 reverse agonists to maximize therapeutic benefit while minimizing central adverse effects. The adverse neuropsychiatric outcomes associated with first-generation agents such as Rimonabant including anxiety, depression, and suicidal ideation highlighted the critical role of central CB1 receptors in mood regulation. Consequently, drug development strategies have shifted toward peripherally restricted CB1 reverse agonists that exhibit limited blood–brain barrier penetration. These agents selectively target CB1 receptors in metabolic tissues such as the liver, adipose tissue, pancreas, and gastrointestinal tract, thereby preserving central endocannabinoid signaling. Preclinical and early clinical studies of second-generation compounds, such as JD5037 and TM38837, have demonstrated promising results in improving insulin sensitivity, reducing hepatic steatosis, and promoting weight loss without significant central nervous system side effects. Mechanistically, these agents modulate key metabolic pathways, including decreased lipogenesis, enhanced fatty acid oxidation, and improved leptin sensitivity. Additionally, emerging third-generation approaches explore biased signaling and allosteric modulation of CB1 receptors, aiming to fine-tune receptor activity rather than completely suppress it. This nuanced control may further reduce adverse effects while maintaining efficacy. Despite these advances, several challenges remain, including long-term safety validation, variability in patient response, and regulatory hurdles. Moreover, a deeper understanding of the endocannabinoid system’s complex role in human physiology is essential for optimizing therapeutic strategies. As of 2026, CB1-targeted therapies continue to evolve, with peripherally selective and functionally selective agents representing a promising frontier in the treatment of obesity, metabolic syndrome, and related disorders.
Keywords: CB1 receptors; CB1 reverse agonists; Rimonabant; agonists; neuropsychiatric